INFORMATION TECHNOLOGY: pensando o futuro sob o olhar da ética - Dias, Robinson Alves; Henrique Del Vechio, Gustavo (Revista Interface Tecnológica, 2023)
This article examines the technological revolution of the 21st century and its relationship to the ethics of information technology and the future of biotechnology. The objective is to study how the concepts of artificial intelligence, cloud computing, Internet of Things and virtual reality are an increasingly integral part of everyday life in modern societies, remodeling the way human beings live in society, understand the world, think, communicate, work and design their future. However, this technological revolution also raises ethical and social questions, as the indiscriminate use of technology can worsen inequality, increase unemployment and compromise data privacy. Therefore, in order to achieve the proposed study objective, as a methodology, a bibliographic review capable of evaluating emerging technologies and the principle of ethics and social justice is proposed. What can be seen from this study is that the technological revolution changes society, while information technology plays an important role in these changes; however, understanding and ethical principles are fundamental to navigating this changing environment and ensuring that modern technologies are applied for the common good, prioritizing ethical and sustainable use.